Making sense of the politics of sanitation in Cape Town. (2nd January 2018) - Jackson, Shannon; Robins, Steven
Abstract: The paper examines the history and politics of sanitation and urban belonging and citizenship in Cape Town. It traces the cultural histories of waste and odour in order to reveal the embedding of liberal citizenship, as well as technology, in the body. We do this to make sense of why and how toilets and waste have become recent objects and instruments of struggle in Cape Town, and elsewhere. The paper shows that these political struggles did not arise from nowhere; their emergence is the outcome of historically and materially sustained contradictions that are fundamental to liberal governance.